KAJIAN PENGGUNAAN BEBERAPA JENIS ENSILING SEBAGAI PENGAWET ALAMI TERHADAP SIFAT KIMIA DAN MIKROBIOLOGIS CAKALANG (Katsuwonus pelamis L) ASAP - Naema Bora (Politeknik Pertanian Negeri Kupang, 2010)
Study the Use of Several Ensiling Types as Natural Preservatives to Increase the Chemical and microbiological Characteristics of Smoked Skipjack Tuna (Katsuwonus pelamis L). The research was conducted in the Managing of Fisheries Product Processing Laboratory, University of Sam Ratulangi Manado in order to determine the effect of ensiling types and storage durations on chemical and microbiological characteristics of smoked skipjack tuna. The research used experimental method that was arranged factorially in 4x4, using Completely Randomized Design (CRD), with two replications in order to obtain 32 experimental units. The treatments consisted of two factors, i.e. types of ensiling (factor A) and storage durations (factor B). Factor A was A0 = without ensiling (as control), A1 = ensiling of mustard green, A2 = ensiling of cabbage, and A3 = ensiling of petsai. Factor B was 0 day, 3 days, 6 days, and 9 days. The observed parameters were water content, pH, total acid, total bacteria (TPC), total lactic acid bacteria, and total fungal colony. The results showed that the effect of cabbage ensiling to the chemical and microbiological characteristics of smoked skipjack tuna was better than the other treatments. It can be recognized from the low value of water content (39.78%) and pH (5.00) as well as the high value of total acid (1.03%), in which, it could support the growth of lactic acid bacteria (3.41 cfu / g) and suppress the growth of bacteria (TPC) and fungi. Ensiling of cabbage can be used as natural preservative to maintain the quality and durability of smoked skipjack tuna. It is recommended that further studies are required to identify lactic acid bacteria and to analyze nutrient content in smoked skipjack tuna as the result of certain ensiling utilization in relation to storing duration.Keywords: storage duration, chemical and microbiological characteristics, smoked skipjack tuna, ensilingStudy the Use of Several Ensiling Types as Natural Preservatives toIncrease the Chemical and microbiological Characteristics of SmokedSkipjack Tuna (Katsuwonus pelamis L). The research was conducted in theManaging of Fisheries Product Processing Laboratory, University of SamRatulangi Manado in order to determine the effect of ensiling types and storagedurations on chemical and microbiological characteristics of smoked skipjacktuna. The research used experimental method that was arranged factorially in4x4, using Completely Randomized Design (CRD), with two replications in orderto obtain 32 experimental units. The treatments consisted of two factors, i.e.types of ensiling (factor A) and storage durations (factor B). Factor A was A0 =without ensiling (as control), A1 = ensiling of mustard green, A2 = ensiling ofcabbage, and A3 = ensiling of petsai. Factor B was 0 day, 3 days, 6 days, and 9days. The observed parameters were water content, pH, total acid, total bacteria(TPC), total lactic acid bacteria, and total fungal colony. The results showed thatthe effect of cabbage ensiling to the chemical and microbiological characteristicsof smoked skipjack tuna was better than the other treatments. It can berecognized from the low value of water content (39.78%) and pH (5.00) as well asthe high value of total acid (1.03%), in which, it could support the growth of lacticacid bacteria (3.41 cfu / g) and suppress the growth of bacteria (TPC) and fungi.Ensiling of cabbage can be used as natural preservative to maintain the qualityand durability of smoked skipjack tuna. It is recommended that further studiesare required to identify lactic acid bacteria and to analyze nutrient content insmoked skipjack tuna as the result of certain ensiling utilization in relation tostoring duration.Keywords: storage duration, chemical and microbiological characteristics,smoked skipjack tuna, ensiling